Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Political crisis in Russia; accusations of corruption against the Vice President: Joint meeting of the Council of Republics and the Council of Nationalities of the Supreme Soviet of the Russian Federation; deputy head of the Supreme Soviet IUrii Voronin meets with a local professional organization. Featured in the program: Birnshtein, Boris (Politician) Contributors: Berdnikova, Nina (Anchor) Политический кризис в России; обвинение вице-президента Александра Руцкого в коррупции; совместное заседание Совета Республик и Совета Национальностей Верховного Совета Российской Федерации; встреча отраслевых и региональных профобъединений с заместителем председателя Верховного совета Юрием Ворониным. В программе участвуют: Бирнштейн, Борис (Политический деятель) Создатели: Бердникова, Нина (Ведущий/Ведущая)